Comparative use of the Ages and Stages Questionnaires in low‐ and middle‐income countries. (21st June 2018) - Small, Jason W; Hix‐Small, Hollie; Vargas‐Baron, Emily; Marks, Kevin P
Abstract : Aim: To map the breadth of use of the Ages and Stages Questionnaires (ASQ) in low‐ and middle‐income countries (LMICs) across world regions, and examine procedures for ASQ translation, adaptation, psychometric evaluation, and administration. Method: We conducted a review of all original, peer‐reviewed studies written in English referencing use of the ASQ in LMICs. We used a consensus rating procedure to classify each article into one of four categories: feasibility study, psychometric study, prevalence study, or research study. Results: We analysed 53 peer‐reviewed articles written in English detailing use of the ASQ in LMICs. We found evidence of ASQ use in 23 LMICs distributed across all world regions. The ASQ was translated into 16 languages. Just over half of the studies reported parent completion of the ASQ (50.9%). We identified eight feasibility studies, 12 psychometric studies, and nine prevalence studies. Study type varied by economy and region. Interpretation: Findings suggest broad global use of the ASQ in a range of countries and cultural and linguistic contexts. There is need for further validation studies across all cited regions and countries and in countries ready to begin to design systems for providing universal developmental screening services. What this paper adds: The Ages and Stages Questionnaires (ASQ) has been used in at least 23 low‐ and middle‐income countries (LMICs). The ASQ has been translated into at least 16 languages in LMICs. Over half the identified studies reported parent completion of the ASQ. What this paper adds: The Ages and Stages Questionnaires (ASQ) has been used in at least 23 low‐ and middle‐income countries (LMICs). The ASQ has been translated into at least 16 languages in LMICs. Over half the identified studies reported parent completion of the ASQ. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations.